Transition-metal, organic solvent and base free α-hydroxylation of β-keto esters and β-keto amides with peroxides in water. Issue 28 (12th July 2019) - Wang, Yakun; Wang, Shuaifei; Gao, Qinghe; Li, Luohao; Zhi, Haoyu; Zhang, Tao; Zhang, Jixia
Abstract: Without employing any transition metal, organic solvent and base, a facile, economical and environmentally friendly strategy has been developed for the α-hydroxylation of β-keto esters and β-keto amides with peroxides via radical cross-coupling reaction in water under open-air conditions. This protocol allows a convenient access to various α-hydroxy-β-keto esters and α-hydroxy-β-keto amides with up to 92% yield (34 examples). Moreover, the reaction was successfully scaled up to gram quantity and mechanistic studies showed the radical pathway was involved in this hydroxylation. Graphical abstract: Without employing any transition metal, organic solvent and base, a facile strategy has been developed for the α-hydroxylation of β-keto esters and β-keto amides with peroxides via radical cross-coupling reaction in water.Image 1